Neuron-specific protein interactions of Drosophila CASK-β are revealed by mass spectrometry - Mukherjee, Konark; Slawson, Justin B.; Christmann, Bethany L.; Griffith, Leslie C. (Frontiers in Molecular Neuroscience, 2014)
Modular scaffolding proteins are designed to have multiple interactors. CASK, a member of the membrane-associated guanylate kinase (MAGUK) superfamily, has been shown to have roles in many tissues, including neurons and epithelia. It is likely that the set of proteins it interacts with is different in each of these diverse tissues. In this study we asked if within the Drosophila central nervous system, there were neuron-specific sets of CASK-interacting proteins. A YFP-tagged CASK-β transgene was expressed in genetically defined subsets of neurons in the Drosophila brain known to be important for CASK function, and proteins present in an anti-GFP immunoprecipitation were identified by mass spectrometry. Each subset of neurons had a distinct set of interacting proteins, suggesting that CASK participates in multiple protein networks and that these networks may be different in different neuronal circuits. One common set of proteins was associated with mitochondria, and we show here that endogenous CASK-β co-purifies with mitochondria. We also determined CASK-β posttranslational modifications for one cell type, supporting the idea that this technique can be used to assess cell- and circuit-specific protein modifications as well as protein interaction networks.